Accounting and Auditing of Costs and Costing of Military Products during Martial Law and Post-War Reconstruction: Institutional Aspect - Viktoria Yatsenko (Облік і фінанси)
The war in Ukraine has revived the discussion on the institutionalization of accounting and auditing and the social and political nature of accounting data generated by the accounting system of an enterprise. In wartime, the role and significance of accounting and auditing change dramatically; they can become instruments for regulating vital processes that can ensure the passage of a difficult period and the achievement of a positive result, or, conversely, can be tools for manipulation, the growth of corruption and betrayal of national interests. Therefore, researchers should pay special attention to cost accounting methods, techniques for calculating the cost of military products, and accountants' role in managing enterprises, institutions, companies and society. The article aims to study the process of institutionalizing accounting and auditing in the context of a broad transformation of society during martial law and post-war reconstruction using the example of the relationship between accounting and auditing with enterprises, state administration and civil society. Based on the study of the experience of Western countries during the WWI and WWII, the article assesses the impact of processes and factors, as well as mechanisms of pressure from conflicting interests on accounting as a technical practice during and after martial law. In addition, the article examines the reverse impact of accounting as a social and political practice on the corporate policy and culture of the enterprise, state administration, and the activities of public and professional organizations. The results of the study show that accounting adapts to wartime conditions and, at the same time, affects enterprise management; war creates a "window of opportunity" for the transformation of accounting; evolutionary changes in accounting occur as a result of the implementation of the country's political course and government activities or the resistance that enterprises put up to pressure from government structures. In martial law and post-war reconstruction conditions, the social role of accounting and social control (audit) is strengthened. Professional institutes of accountants and auditors should become active agents of social control and auditing of the activities of business structures and state bodies to ensure compliance with civil society standards. On the other hand, the activities of representatives of the profession should be regulated by social standards established by the professional institutions themselves.